Flow and climatic variability on a Southamerican mid-latitude basin: río Aconcagua, central Chile (33ºS) - Carolina Martínez; Alfonso Fernández; Patricio Rubio (Boletín de la Asociación de Geógrafos Españoles, 2012)
Resumen